The third term of the expansion is 6a^2b^2
<h3>How to determine the third term of the
expansion?</h3>
The binomial term is given as
(a - b)^4
The r-th term of the expansion is calculated using
r-th term = C(n, r - 1) * x^(n - r + 1) * y^(r - 1)
So, we have
3rd term = C(4, 3 - 1) * (a)^(4 - 3 + 1) * (-b)^(3-1)
Evaluate the sum and the difference
3rd term = C(4, 2) * (a)^2 * (-b)^2
Evaluate the exponents
3rd term = C(4, 2) * a^2b^2
Evaluate the combination expression
3rd term = 6 * a^2b^2
Evaluate the product
3rd term = 6a^2b^2
Hence, the third term of the expansion is 6a^2b^2
Read more about binomial expansion at
brainly.com/question/13602562
#SPJ1
Answer:
21.2 yd
Step-by-step explanation:
8 + 6 + 7.2 = 14 + 7.2 = 21.2
Answer: 25 in
Step-by-step explanation:
<u>Due to the use of the term "hypotenuse" I will assume the triangle is a right triangle.</u>
<u></u>
According to pythagorean theorem, 7²+24²=(hypotenuse)²
49+24²= (hypotenuse)²
49+576= (hypotenuse)²
625 = (hypotenuse)²
25 = hypotenuse
Hope it helps <3 :D
22 is the answer because I just did it
Energy is either released or absorbed